PENGARUH SARANA PENDIDIKAN TERHADAP EFEKTIVITAS PROSES PEMBELAJARAN S1 PROGRAM STUDI PENDIDIKAN EKONOMI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Solin, Harpen Putra; Nas, Syakdanur; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack: This research aims to know the influence of education against the effectiveness of the learning process of economic education courses Undergraduate Faculty of teacher training and educational sciences of the University of Riau. The population in this research is active students host 2013 – 2016 as much as 330 peoples, and become a sample as many as 77 people. Measurement data using the question form and documentation. The analysis of the data used is a simple linear regression. Research results based on simple linear regression shows the use of educational means to keefektivan the process of learning and PEDAGOGY in Education undergraduate student of Economics, it can be seen from constanta (a) value of 38.566 and the value of the regression (b) coefisien of regresinya equations with 38.566 0.514 + 0.514. Seen from the calculation of R2 (R Square Change) obtained the value of 0.326. It means is that the donations influence the use of educational means against efektivan the learning process of 32.6%.Key Word : Educations Facilities, Effectiveness of the Learning Process